- Hey, Jasmine. Today I would like to give you an equation for you to solve.
- Sure Jack, I love math equations
- Okay, the math is equation that I would like for you to solve is 2/6(x+2)+5=-2/3(x-9)-8
- Okay, lets go to the study room so I can sit down.
- ....Jasmine goes to the study room and starts solving the equation in front of Jack
- 2/6(x+2)+5= -2/3(x-9)-84/12(x+2)+5= -8/12(x-9)-812*4/12(x+2)+5= 12*-8/12(x-9)-84(x+2)+5= -8(x-9)-84x+8+5= -8x+72-84x-8x=72-8+8+5-4x=77x= -77/4
- However, when you multiply 12 with the fraction in order to get rid of the denominator, you have to multiply all the numbers in that line by 12
- For this equation you made 2 big mistakes.Number 1: Its common knowledge that you need to get rid of the
- as well. Example shown below: 12*(4(x+2))/12 All the variables and numbers in those brackets are multiplied by 12
- You were close, however you made a few mistakes. I will teach you how to properly solve that type of equation.
- denominators on fractions before you can start solving the equation. You chose 12 as your lowest common multiple and that was done nicely.
- Meaning, -8*12 =-96. The final equation for the right side should have been -8x+72-96.
- However it eventually gets cancelled out due to the numbers and variables getting divided by 12.
- In your case, you missed the chance to multiply 5 by 12, resulting in a incorrect equation for the left side.
- The final equation for the left side should have been 4x+8+60Since 5*12 is 60. This also applies to the right side.
- When you move positive variables from the right side to the left side, they become negative. Vice versa.
- The second mistake was near the end. You have to sort the variables to the left side and the numbers to the right side.
- When you move negative numbers from the left side to the right side, they become positive. This also applies to variables.
- What this means is that when you move numbers that are positive from the left side to the right side, it becomes negative.
- Instead of 4x-8x=72-8+8+5,It should have been 4x+8x=72-96-8-60.
- The = sign in the equation differentiates the left side and right side of the equation.
- The correct solution for this equation....
- 2/6(x+2)+5= -2/3(x-9)-84/12(x+2)+5= -8/12(x-9)-812*4/12(x+2)+5= 12*-8/12(x-9)-84(x+2)+60= -8(x-9) - 964x+8+60= -8x+72-964x+8x=72-96-8-6012x=-92x=-92/12Orx= -23/3Or-7 2/3